The Effect Of Receivables Turnover, Capital Structure, Operating Costs, And Company Size On Profitability In Banking Companies Listed On The Indonesia Stock Exchange - Putri Adelia; Nina Andriany Nasution; Meigia Nidya Sari (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aimed to examine the effects of accounts receivable turnover, capital structure, operating costs, and firm size on profitability in banking companies listed on the Indonesia Stock Exchange. The study used secondary data obtained from the official website of the Indonesia Stock Exchange, namely www.idx.co.id. The research data consisted of company financial statement data from 2023–2024. The study was conducted in 2025. The population of this study included all banking companies totaling 47 companies, with a sample of 41 companies, resulting in 82 rows of data used as the sample. This study employed an associative approach with quantitative data. Multiple linear regression analysis was applied using SPSS 24.0 for data processing. The results showed that accounts receivable turnover and firm size partially had a positive and significant effect on profitability, while capital structure partially had a negative and significant effect on profitability, whereas operating costs did not have a significant effect on profitability. Simultaneously, accounts receivable turnover, capital structure, operating costs, and firm size had a positive and significant effect on profitability in banking companies. Accounts receivable turnover became the most influential variable on profitability. Accounts receivable turnover, capital structure, operating costs, and firm size contributed 52.4% to profitability. Accounts receivable turnover, capital structure, operating costs, and firm size had a strong relationship with profitability.